Stable Cu Catalysts Supported by Two‐dimensional SiO2 with Strong Metal–Support Interaction (Adv. Sci. 9/2022). Issue 9 (25th March 2022) - Wang, Shenghua; Feng, Kai; Zhang, Dake; Yang, Deren; Xiao, Mengqi; Zhang, Chengcheng; He, Le; Yan, Binhang; Ozin, Geoffrey A.; Sun, Wei
Abstract : Stable Cu Catalysts In article number 2104972, Binhang Yan, Wei Sun, and co‐workers design a stable Cu/2DSiO2 catalyst with strong metal–support interaction for high‐temperature CO2 reduction. The "beads‐in‐a‐book" structure is derived through growth of Cu between 2D Si nanosheets. The authors believe that this work could stimulate more interest in constructing stable metal catalysts with 2DSiO2 .